2016
DOI: 10.1111/jcpp.12544
|View full text |Cite
|
Sign up to set email alerts
|

Does comorbid anxiety counteract emotion recognition deficits in conduct disorder?

Abstract: Background: Previous research has reported altered emotion recognition in both conduct disorder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
(83 reference statements)
3
18
0
Order By: Relevance
“…CD was also associated with impaired fear recognition. These findings support previous research demonstrating impaired recognition of anger and fear in adolescents with CD (Bowen et al, 2013;Fairchild et al, 2009Fairchild et al, , 2010Short et al, 2016;Sully et al, 2015). Critically, our work extends these previous findings by demonstrating that anger and fear recognition deficits are still present when the stimuli are dynamic or presented at lower intensity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CD was also associated with impaired fear recognition. These findings support previous research demonstrating impaired recognition of anger and fear in adolescents with CD (Bowen et al, 2013;Fairchild et al, 2009Fairchild et al, , 2010Short et al, 2016;Sully et al, 2015). Critically, our work extends these previous findings by demonstrating that anger and fear recognition deficits are still present when the stimuli are dynamic or presented at lower intensity.…”
Section: Discussionsupporting
confidence: 91%
“…However, CD is associated with similar neuropsychological impairments in males and females, including lower verbal IQ (Lynam, Moffitt, & Stouthamer-Loeber, 1993;Moffitt & Silva, 1988;Pajer et al, 2008), deficits in autonomic fear conditioning (Fairchild, Stobbe, van Goozen, Calder, & Goodyer, 2010;Fairchild, Van Goozen, Stollery, & Goodyer, 2008) and reduced eye-blink startle responses (Fairchild et al, 2008(Fairchild et al, , 2010. While research has demonstrated that CD is associated with impairments in facial emotion recognition in males and females (Fairchild, Van Goozen, Calder, Stollery, & Goodyer, 2009;Fairchild et al, 2010;Schwenck et al, 2012Schwenck et al, , 2014Short, Sonuga-Barke, Adams, & Fairchild, 2016;Sully, Sonuga-Barke, & Fairchild, 2015), the underlying cause(s) of these deficits are not well understood. They could reflect difficulties with attention (e.g., impaired orienting to the eye region of the face) and/or appraisal (interpretation of stimuli that have been successfully encoded).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically Prado and colleagues [42], used the Levenson self-report measure at a single time point to identify primary and secondary groups, whereas we used a combination of measures of conduct problems, callous unemotional traits and anxiety, assessed over time. As indicated by the accuracy ratings, our findings also suggest that this impairment in facial affect recognition for individuals high on CU traits is more generalized, in line with meta-analytic findings [19] and a study conducted with adolescents with CP (with and without anxiety); [3] that emotion recognition deficits in psychopathy are not restricted to specific emotions such as fear or sadness as has been suggested by prior work [5,17,43]. The stimuli used in the current study were dynamic snapshots (clips) of adults expressing various emotions and included movements in different parts of the face compared to static stimuli that were used in other studies [5,24] possibly contributing to the differences in results.…”
Section: Discussionsupporting
confidence: 88%
“…We also hypothesized that participants with CD/CU+ would show reduced EA, emotion recognition, and affective empathy relative to CD/CU- participants. We predicted that such deficits would be particularly marked for sadness and fear, given previous research showing disproportionate impairments in the processing of distress cues in those with high levels of CU traits (Dadds et al 2006 ; Marsh and Blair 2008 ; Short et al 2016 ).…”
Section: The Current Studymentioning
confidence: 98%
“…It has been proposed that empathy is a multi-faceted phenomenon that can be fractionated into at least three forms: cognitive empathy (understanding others’ mental states/emotion recognition), affective empathy (feeling the same emotion as another person), and motor empathy (mirroring others’ body movements and facial expressions; Blair 2005 ). There is increasing evidence that individuals with Disruptive Behavior Disorders (DBDs) such as Conduct Disorder (CD) and Oppositional Defiant Disorder (ODD), show deficits in emotion recognition (Fairchild et al 2009 ; Short et al 2016 ) and affective empathy (de Wied et al 2005 ; de Wied et al 2012 ). Nevertheless, findings are inconsistent across studies and highly simplified stimuli or tasks have been used in many of these studies.…”
mentioning
confidence: 99%